Penerapan Logika Fuzzy Pada Exhaust Fan Otomatis Berdasarkan Kadar Polusi Udara Dalam Ruangan Menggunakan Metode Sugeno - Rama Sapto Pamungkas (2020)
Currently, some people still do not know about the dangers of indoor air pollution. Many things can affect the quality of indoor air, especially in the kitchen of households that often occur in the combustion, such as the failure to discharge harmful gases such as CO_2, CO, and C_6 H_6. Usually people use exhaust fan to resolve the problem. However, exhaust fan only rotates at a fixed speed and must manually turn on it can be said to be not optimal. There is usually a condition in the room enough with a slight speed of exhaust fan to maintain air circulation. From the problem, the need for a system that can control the speed of exhaust fan automatically based on air pollution gas levels such as CO_2, CO, and C_6 H_6. The system uses two sensors to detect gas as the input value for the exhaust fan output speed. The types of sensors used are sensor MQ - 135 and Sensor MQ - 7. The system uses fuzzy logic with the Takagi-Sugeno-Kang method and for the method of looking for its output value or called Defuzzification using the Weight hotel method. The MSE value obtained at the idle stove condition is 0. While the value of MSE at the time of the stove is lit one is 1.2353, the stove lit two 0.56644.